DETERMINAN FAKTOR LOYALITAS KARYAWAN PT. BUMI KONAWE MINERINA - TONDATUAN, ALYCIA GRACE; NURMIATI, NURMIATI (Patria Artha Management Journal, 2025)
This study aims to analyze the impact of effective communication, work environment, and job satisfaction on employee loyalty in the mining industry, with a case study at PT. Bumi Konawe Minerina. The mining industry faces significant challenges in maintaining employee loyalty, which can be influenced by communication factors, work environment, and job satisfaction. This research employs a quantitative method using a survey approach targeting employees. The analysis results indicate that effective communication, a conducive work environment, and job satisfaction significantly contribute to increased employee loyalty. These findings provide recommendations for companies in designing strategies to enhance employee loyalty through more open communication, a supportive work environment, and better employee welfare policies.